Development of the starting reaction of track and field sprinters using sensory-motor means - Vinogradova, O. P.; Morozova, L. V.; Melnikova, T. I. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to substantiate the development of the starting reaction using sensory-motor means of special training for female sprinters.